Optimization of flight distance and robustness in the discus - Seo, K.; Shimoyama, K.; Ohta, K.; Ohgi, Y.; Kimura, Y. (Sports Engineering, 2015)
This paper describes the optimal flight of a discus. Two objective functions are considered. One is the flight distance, and the other is robustness. Robustness is defined as insensitivity to deviations from the local optimal release conditions. The aim of the optimization is to maximize both flight distance and robustness. There are ten control and design variables, which include variables concerned with the skill of the thrower and with the design of the equipment. It was found that there is a trade-off between flight distance and robustness. It was also found that lower drag is preferable in the first half of flight, and greater lift and drag are preferable in the latter half of flight for the world record throw of 77 m. In order to do this, the initial angle between the velocity vector and the discus planform should be negative at the launch, even if the initial lift acts vertically downward. The attitude of the discus should be inclined at launch. The discus rolls with time during the flight, so that the discus planform becomes almost in the horizontal plane in the latter half of the flight. Lower mass is good for achieving longer flight distance, but conversely, mass should be slightly greater for robustness.